Viroporins: structure and biological functions - Nieva, José Luis; Madan Renes, Vanesa; Carrasco, Luis (Nature reviews. Microbiology, 2012)
Viroporins are small, hydrophobic proteins that are encoded by a wide range of clinically relevant animal viruses. When these proteins oligomerize in host cell membranes, they form hydrophilic pores that disrupt a number of physiological properties of the cell. Viroporins are crucial for viral pathogenicity owing to their involvement in several diverse steps of the viral life cycle. Thus, these viral proteins, which include influenza A virus matrix protein 2 (M2), HIV-1 viral protein U (Vpu) and hepatitis C virus p7, represent ideal targets for therapeutic intervention, and several compounds that block their pore-forming activity have been identified. Here, we review recent studies in the field that have advanced our knowledge of the structure and function of this expanding family of viral proteins.